FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS DI KOTA PEKANBARU - Hutabarat, Roy Hendra; Ratnawati, Vince; Julita, Julita (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2018)
The purpose of this research is to analyze the influence of the awareness of paying taxes, knowledge of tax regulations, good perception on tax system effectiveness, quality of tax service, tax understanding and the assertion of tax sanction against willingness to pay taxes of an individual taxpayer that doing free work. The population of this research is taxpayers who perform free work in Pekanbaru City in 2016 as many as 78,191 people, sample taken by accidental sampling method. To determine the number of samples was using Slovin formula so that the total sample is 100 people. While the data analysis using multiple linear regression. The result indicates that taxpayers' awareness, taxpayers’ knowledge about tax regulation, tax service quality, taxpayer understanding about taxation, and tax sanction partially have significant influences on the willingness to pay tax of taxpayers who do free work in Pekanbaru. Meanwhile, the perception of taxpayers do not have a significant influence on that matter.